Advanced Glycation End Products Inhibitors from Talisia esculenta - Alves, Natalia Felix [UNESP]; Ribeiro, Dayane Castro [UNESP]; Mannochio-Russo, Helena [UNESP]; Queiroz, Suzana Aparecida Silva [UNESP]; Zocolo, Guilherme Juliao; Bolzani, Vanderlan da Silva [UNESP]; Valli, Marilia (Soc Brasileira Quimica, 2023)
Advanced Glycation End Products (AGEs) are formed under hyperglycemic conditions but also during the natural aging process. AGEs are associated with skin aging, loss of skin elasticity, and some chronic diseases such as diabetes and Alzheimer ' s, being a research topic of great relevance. Several herbal supplements have beneficial effects on glycemic control and oxidative stress, with the consequent reduction in the volume of AGEs during aging. In this scenario, the search for natural products with AGEs inhibition activity has been gaining prominence due to their importance for innovation in pharmaceuticals and cosmetics. The present study describes the investigation of natural products from Talisia esculenta with antiglycation activity. Ten phenolic compounds were annotated by LC-MS, and the compounds present in the leaves extracts were isolated, characterized by NMR and submitted for further in vitro studies. Rutin and quercitrin were isolated and presented 44% and 86% antiglycation activity at 150 mu g/mL. These results open new possibilities for the use of abundant natural compounds as AGEs inhibitors, and further studies should be performed to evaluate their use and efficacy in cosmetics formulations and even in the treatment of AGEs-associated diseases.
Keywords: Advanced glycation; natural products; Talisia esculenta; Sapindaceae; bioeconomy